1987
DOI: 10.1002/qj.49711347609
|View full text |Cite
|
Sign up to set email alerts
|

Water Vapour Transport Over Africa and the Atlantic Ocean During Summer 1979

Abstract: The water vapour transport over Africa and the eastern Atlantic Ocean during the 1979 summer is studied. The analysis is based on wind fields from the European Centre for Medium Range Weather Forecasts and humidity fields derived from a three-layer precipitable water data set.The evolution of the bi-weekly mean fields of water vapour flux in the surface to 850mb layer shows the progressive penetration of moisture over West Africa during the summer. At low levels during the maximum activity of the African monso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(24 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…Fontaine et al [2003], using NCEP-NCAR Reanalysis, identified the Sudanian and Guinean regions as sink areas in JAS and emphasized the weight of moisture advection in the interannual variability of rainfall. Their results are consistent with those of Cadet and Nnoli [1987] and Gong and Eltahir [1996], but in contrast with those of Brubaker et al [1993], Nicholson et al [1997], and also more recently Nieto et al [2006], who support the idea that recycling represents a significant contribution to the annual mean and interannual variability.…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…Fontaine et al [2003], using NCEP-NCAR Reanalysis, identified the Sudanian and Guinean regions as sink areas in JAS and emphasized the weight of moisture advection in the interannual variability of rainfall. Their results are consistent with those of Cadet and Nnoli [1987] and Gong and Eltahir [1996], but in contrast with those of Brubaker et al [1993], Nicholson et al [1997], and also more recently Nieto et al [2006], who support the idea that recycling represents a significant contribution to the annual mean and interannual variability.…”
Section: Introductionsupporting
confidence: 85%
“…[43] Using a similar approach, Cadet and Nnoli [1987] estimate E as a residual and find also too large values (around 10 mm d −1 ) in the Sudanian zone in JAS. More recent studies using NWP model simulations found contrasting results.…”
Section: Annual Mean and Seasonal Cyclesupporting
confidence: 74%
See 2 more Smart Citations
“…Especially, the density of radiosonde stations in Africa is very sparse [Parker et al, 2008]. Moreover, biases in these observations have been diagnosed and their impact on NWP products has been evidenced Agustí-Panareda et al, 2009], It is thus not surprising that poor consensus emerged from the past water cycle studies over West Africa which used either NWP products or directly radiosonde data [Lamb, 1983;Cadet and Nnoli, 1987;Brubaker et al, 1993;Fontaine et al, 2003;Bielli and Roca, 2009].…”
Section: Introductionmentioning
confidence: 99%